Inventando deusas / outra religião: os sentidos elaborados por pastoras feministas e dissidentes do sexo/gênero - Nascimento, Louise Tavares Oliveira do (2024)
This work aimed to note, through an approximation witch pastoral, the meanings elaborated by feminist reverends and sex/gender dissidents, which are aligned with the progressive evangelical field. For this, this research sought to approach the pastors Ana Ester, Alexya Salvador and Odja Barros who have been working in affirmative churches, places where LGBTQIAPN+ people can be an active in ecclesial body. The pastors themselves are part of the movement, Ana Ester and Alexya Salvador, who claim to be lesbian and transvestite, respectively, while pastor Odja Barros, even though she is heterosexual, acts as a feminist and ally of the cause. Thus, by defining their actions through an agenda of affirmative faith and feminists, there was a need to understand the relationships they establish between religiosity, gender and sexual diversity. A topic that is being debated, given the clashes promoted by conservatives and evangelical fundamentalists, in a context where the boundaries between politics and religion are controversial. Therefore, this dissertation seeks to understand how the transformations that these women seek to develop re-elaborate the meanings of the Christian tradition, in the face of patriarchal and oppressive logics. For this, this study prioritized the production of an ethnography that took place virtually, glimpsing the conceptions given through research on etnography virtual. The techniques used prioritize the monitoring of social networks, the application of interviews, focusing on life stories and pastoral activity, as well as the analysis of the material and productions of these pastors available on the internet, that is, videos, sermons, texts and books. Finally, through this information, a reflection was made on the subject in anthropological terms, in relation to the field of gender and sexuality, and the Anthropology of Religion. In fact, it was possible to notice a wide academic production and circulation in the public environment of these women. Between book publications, preaching, Bible studies, journalistic articles, participation in congresses and seminars, a transit between the religious and academic environments is perceptible. In addition, in the faith practices of the reverends, the approximation and construction of an emancipatory pedagogy in which feminisms and spirituality – together – is material for the transformation they seek to undertake, is notorious. Finally, it was very promising to note how life, preaching and pastoral work are intertwined in the actions of these pastors who seek meanings of a faith committed to social justice, the end of inequality and promotion of diversity. Even so, this work does not shy away from a reflection on the challenges faced by them, which takes place in a process with ruptures, tensions and power relations implied in the evangelical milieu.